2003
DOI: 10.1007/s00216-003-2174-9
|View full text |Cite
|
Sign up to set email alerts
|

Cholinesterase sensors based on screen-printed electrodes for detection of organophosphorus and carbamic pesticides

Abstract: Cholinesterase sensors based on screen-printed electrodes modified with polyaniline, 7,7',8,8'-tetracyanoquinodimethane (TCNQ), and Prussian blue have been developed and tested for detection of anticholinesterase pesticides in aqueous solution and in spiked grape juice. The influence of enzyme source and detection mode on biosensor performance was explored. It was shown that modification of the electrodes results in significant improvement of their analytical characteristics for pesticide determination. Thus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 34 publications
(41 reference statements)
3
35
0
2
Order By: Relevance
“…The enzymatic activity can be detected by means of the oxygen decrease measurement using Clark's electrode 64 or the increase of hydrogen peroxide 65 which can be measured amperometrically at around +600 mV versus Ag/AgCl using a platinum electrode. Moreover it is possible to achieve the decreasing of the applied potential by using of redox mediators, such as prussian blue 66,67 , ferophthalocyanine 68 , or by adopting novel materials such as carbon nanotubes 69,70 . Multi-walled carbon nanotubes-modified screen-printed carbon electrodes offer a significant catalytic effect for the reduction and oxidation of hydrogen peroxide 70 .…”
Section: Electrochemical Biosensorsmentioning
confidence: 99%
“…The enzymatic activity can be detected by means of the oxygen decrease measurement using Clark's electrode 64 or the increase of hydrogen peroxide 65 which can be measured amperometrically at around +600 mV versus Ag/AgCl using a platinum electrode. Moreover it is possible to achieve the decreasing of the applied potential by using of redox mediators, such as prussian blue 66,67 , ferophthalocyanine 68 , or by adopting novel materials such as carbon nanotubes 69,70 . Multi-walled carbon nanotubes-modified screen-printed carbon electrodes offer a significant catalytic effect for the reduction and oxidation of hydrogen peroxide 70 .…”
Section: Electrochemical Biosensorsmentioning
confidence: 99%
“…In case of cholinesterase biosensors it is possible to lower the voltage and interferences of electroactive sample components by means of redox transmitters such as ferophtalocyanine, cobalt phtalocyanine, Prussian blue (ferrihexacyanofferate), 7,7,8, in combination with carbon electrodes, screen electrodes or using the carbon nanotube (CNT) (Arduini et al, 2007;Ciucu et. al., 2003;Hart et al, 1997;Hernandez et al, 2000;Lin et al, 2004;Ricci et al, 2003;Ivanov et al, 2003a;Nunes et al, 2004;Shulga & Kirchhoff, 2007;Skládal, 1992;Skládal & Mascini, 1992;Suprun et al, 2005;Wring et al, 1989) or electrochemical decomposition of the arising peroxide using a gold or platinum amperometric electrode (Yao, 1983). CNTs are commonly used for electrochemical biosensors.…”
Section: Amperometric Biosensorsmentioning
confidence: 99%
“…ChE immobilization was able to carry out by cross-linking method with glutaraldehyde vapour (Arkhypova et al, 2003(Arkhypova et al, , 2004(Arkhypova et al, and 2008. It was reported a ChE membrane formed on the electrode with ChE, Nafion and glutaraldehyde (Suprun et al, 2005;Ivanov et al, 2003). In this case, it was found that the use of albumin bovine serum at 3% increases the enzyme stability (Arduini et al, 2006;Laschi et al 2007).…”
Section: Covalent Attachmentmentioning
confidence: 99%